2020
DOI: 10.3390/genes11101140
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variant Filtering for Mitochondrial Genome Haplotype Reporting

Abstract: Given the enhanced discriminatory power of the mitochondrial DNA (mtDNA) genome (mitogenome) over the commonly sequenced control region (CR) portion, the scientific merit of mitogenome sequencing is generally accepted. However, many laboratories remain beholden to CR sequencing due to privacy policies and legal requirements restricting the use of disease information or coding region (codR) information. In this report, we present an approach to obviate the reporting of sensitive codR data in forensic haplotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Notably, four of our study participants carried mtDNA variants previously confirmed to be associated with LHON or deafness. This is in line with findings from previous studies that have reported these and other pathogenic mtDNA variants in the general population at varying levels of heteroplasmy (4.4–100.0%) ( Elliott et al, 2008 ; Venter et al, 2019 ; Marshall et al, 2020 ). To the best of our knowledge, none of the individuals carrying these mtDNA variants were affected by either of these conditions, reinforcing the well-accepted notion that additional genetic (i.e., mtDNA and nDNA backgrounds) and environmental factors [e.g., exposure to aminoglycoside antibiotics that induce non-syndromic deafness in carriers of the m.1555A > G variant ( Ou et al, 2018 )] may play a role in the expression of a mtDNA-associated disease phenotype ( Khan et al, 2017 ; Wei et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, four of our study participants carried mtDNA variants previously confirmed to be associated with LHON or deafness. This is in line with findings from previous studies that have reported these and other pathogenic mtDNA variants in the general population at varying levels of heteroplasmy (4.4–100.0%) ( Elliott et al, 2008 ; Venter et al, 2019 ; Marshall et al, 2020 ). To the best of our knowledge, none of the individuals carrying these mtDNA variants were affected by either of these conditions, reinforcing the well-accepted notion that additional genetic (i.e., mtDNA and nDNA backgrounds) and environmental factors [e.g., exposure to aminoglycoside antibiotics that induce non-syndromic deafness in carriers of the m.1555A > G variant ( Ou et al, 2018 )] may play a role in the expression of a mtDNA-associated disease phenotype ( Khan et al, 2017 ; Wei et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…The limitation, however, with the use of microarrays, in addition to requiring a large amount of input DNA, is that they contain potential genetic data with reasonable positive predictive power that could expose personal, privacy information about an individual. Budowle et al, [ 86 ] and Marshall et al [ 87 ] recommended (for whole mitochondrial genome sequence data) those SNPs that may provide such information could be filtered so only SNPs with little or no predictive power are reported. However, the raw data would still contain the SNPs which some jurisdictions and stakeholders might consider a risk to privacy.…”
Section: Resultsmentioning
confidence: 99%
“…There are potential ethical issues concerning genetic privacy, such as health‐related mutations in the coding region (Brandhagen et al, 2020; Marshall, Sturk‐Andreaggi, Ring, et al, 2020). While forensic laboratories are not focused on studying genes linked to the predisposition of a disease, this information can be found in mitogenome mtMPS data.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…To overcome this, laboratories will need to develop policies on how to deal with the unintended discovery of medical information (Scudder et al, 2018). Marshall, Sturk‐Andreaggi, Ring, et al (2020), used the MitoMap database to identify 92 mtDNA coding region variants with confirmed pathogenicity. They then searched for the pathogenic variants in EMPOP and found that the frequency of the variants is quite low.…”
Section: Technical Considerationsmentioning
confidence: 99%